CHALLENGES AND OPPORTUNITIES IN THE HIDES AND SKINS SECTOR FOR IMPROVING LIVELIHOODS IN GARISSA SUB-COUNTY, KENYA - Huho, Julius M.; Ng’ang’a, Stephen Irura; Ahmed O. Warfa; Ahmed Maalim; Macharia, Kevin Ng'ang'a; Omillo, Francis; Kennedy Nyaga; Elizabeth Masayi; Wainaina, Peris; Heckman Ochieng (My University, 2025)
Garissa subcounty is located in an Arid and Semi-Arid Land (ASAL) region with a large livestock population, that produces a huge number of hides and skins. This study investigated the challenges and opportunities in the hides and skins sector within the subcounty to inform the interventions for quality improvement and economic empowerment of the pastoral communities. The study employed a descriptive research design, utilizing observation, field surveys and the delphi methods. Data was obtained from flayers, livestock owners and hides and skins traders. Qualitative data was analyzed using content analysis, while descriptive statistics were used for quantitative data. Data was collected from 62 respondents, consisting of 50 flayers, 8 livestock owners and 4 hides and skins traders. Key findings reveal a predominantly male-dominated occupation, with a significant portion of stakeholders possessing low formal education and relying acquisition of skills through apprenticeship. Key challenges identified include the poor quality of hides and skins resulting from inadequate flaying skills and the use of inappropriate tools since the primary focus is on meat production. Other challenges include delayed payments, harsh climatic conditions affecting preservation, poor handling of hides and skins, inadequate facilities and negative perceptions on hides and skins from northeastern parts of Kenya by tanneries. The inadequate market for hides and skins caused them to be discarded since they were perceived as having zero value. Despite these challenges, the sector offers significant opportunities which include the restoration of traditional knowledge on hides and skins for cultural preservation and value addition, the creation of job opportunities for youth and women across the value chain and the local production of affordable leather products like sandals, belts, and bags. The report concludes that despite government initiatives to revitalize the national leather sector, Garissa subcounty’ s hides and skins industry is declining. The current underperformance of the sector represents a missed economic opportunity for the community, highlighting the need for targeted interventions to improve quality, market access, and value chain development.
Keywords: Hides; Skins; Garissa Sub-county; Livelihoods; Pastoralism